2021
DOI: 10.1016/j.vas.2021.100166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean curd residue and rice bran on lamb performance, health, and meat quality

Abstract: Recycling food by-products as animal feed could decrease livestock production costs. We investigated how replacing conventional corn and wheat bran feed (control) with rice bran and soybean curd residue (RBSR) would influence lamb performance and meat quality. Eleven lambs were divided into the control and the RBSR-fed groups. The amount of feed consumed by the lambs, as well as their body weight, nutrient properties (total protein, non-esterified fatty acid, total cholesterol, glucose concentrations) in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…In addition, muscle denaturation reduces the proteins myosin and actin, resulting in softer meat [ 58 ]. Another possible explanation would be the higher content of intermuscular fat [ 59 ] in the meat of the birds belonging to the T-100 group, a factor also related to tenderness [ 60 ]. Lin et al [ 61 ] reported that supplementing 200 and 300 mg/kg of Magnolia officinalis extract decreased water due to cooking loss and increased water retention capacity in duck meat due to its antioxidant effects, retarding lipid and protein oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, muscle denaturation reduces the proteins myosin and actin, resulting in softer meat [ 58 ]. Another possible explanation would be the higher content of intermuscular fat [ 59 ] in the meat of the birds belonging to the T-100 group, a factor also related to tenderness [ 60 ]. Lin et al [ 61 ] reported that supplementing 200 and 300 mg/kg of Magnolia officinalis extract decreased water due to cooking loss and increased water retention capacity in duck meat due to its antioxidant effects, retarding lipid and protein oxidation.…”
Section: Discussionmentioning
confidence: 99%